Research on Key Technology of Online Measurement of Five-axis Linkage Machine Tool - Dashuang Wang; RongJing Hong (Journal of Applied Science and Engineering, 2024)
In order to improve the machining accuracy and online measurement accuracy of the five-axis linkage machine tool, the motion solution of the double pendulum head five-axis linkage machine tool is realized based on the analysis of the movement and change law of the tool position point and the tool axis vector during the five-axis linkage process. Based on the above mathematical model, a calibration technology of online measurement system of five-axis CNC machine tool based on standard ball and three-dimensional probe is proposed. The experimental results verify the validity and accuracy of the calibration method. The online measurement function of 840Dsl CNC system is developed, and the working principle and execution process of coordinate transformation and measurement cycle of five-axis machine tool are deeply studied. Based on the tool center point rotation (RTCP) function of the CNC system, a three-dimensional position transformation alignment technology scheme is proposed, which is lacking in the industry. Through the application of system measurement cycle, macro program function and system variable, the online measurement function of five-axis machine tool is constructed to realize the accurate measurement of workpiece zero point in the manufacturing process. The experiment results show that the measurement efficiency of the parts is improved by 75%, and the qualification rate of the parts is increased to 100% during five-axis machining process. The application of online workpiece measurement method greatly reduces the auxiliary machining time of parts and improves the machining efficiency and accuracy during five-axis machining.